2014
DOI: 10.1371/journal.pone.0087205
|View full text |Cite
|
Sign up to set email alerts
|

The Mechanism of Intralipid®-Mediated Cardioprotection Complex IV Inhibition by the Active Metabolite, Palmitoylcarnitine, Generates Reactive Oxygen Species and Activates Reperfusion Injury Salvage Kinases

Abstract: BackgroundIntralipid® administration at reperfusion elicits protection against myocardial ischemia-reperfusion injury. However, the underlying mechanisms are not fully understood.MethodsSprague-Dawley rat hearts were exposed to 15 min of ischemia and 30 min of reperfusion in the absence or presence of Intralipid® 1% administered at the onset of reperfusion. In separate experiments, the reactive oxygen species (ROS) scavenger N-(2-mercaptopropionyl)-glycine was added either alone or with Intralipid®. Left ventr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
62
0
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(71 citation statements)
references
References 52 publications
6
62
0
3
Order By: Relevance
“…25 Coupled with the observation that infused lipid emulsion activates cardioprotective pathways, this provides an additional mechanism of postconditioning benefit to the local anesthetic-toxic heart. 26,27 The explanations behind these purported benefits are discussed in detail in the supporting article. 10…”
Section: Cardiotonic Effectsmentioning
confidence: 99%
“…25 Coupled with the observation that infused lipid emulsion activates cardioprotective pathways, this provides an additional mechanism of postconditioning benefit to the local anesthetic-toxic heart. 26,27 The explanations behind these purported benefits are discussed in detail in the supporting article. 10…”
Section: Cardiotonic Effectsmentioning
confidence: 99%
“…24 The activation of Akt and inhibition of GSK-3β contribute to prevention of opening of the mPTP; this effect is consistent with studies showing that ILE attenuates IR injury. 112,116,117 Lou et al 118 proposed a mechanism of protection by ILE in IR injury based on accumulation of palmitoylcarnitine, which slightly uncouples mitochondria at complex IVand releases a burst of ROS, which signal RISK activation. Reactive oxygen species can oxidize and inactivate phosphatase and tensin homolog, which leads to hyperphosphorylation of prosurvival kinases, 119 making this a plausible but incompletely tested hypothesis.…”
Section: Postconditioning Benefitmentioning
confidence: 99%
“…124,125 Lipid also modifies signaling in many pathways while functioning as a metabolic fuel. Lipid activates Akt, Erk1/2, and GSK-3b after IR injury, 112,[116][117][118] as well as AMPK in peripheral tissues, 126 and can drive cardiac hypertrophy. 127 Long-term lipid treatment activates PKCy and PKCδ via diacylglycerol to promote insulin resistance.…”
Section: Future Directionsmentioning
confidence: 99%
“…Based on these results, we hypothesize that Intralipid ® has the potential to derail MØs and change the trafficking of MØs in inflammatory heart diseases. Intralipid ® has been shown to protect hearts against ischemic reperfusion injury to reduce infarct size after ischemic insult [21]- [23]. The cardioprotective mechanisms of Intralipid ® are not totally understood.…”
Section: Introductionmentioning
confidence: 99%
“…The cardioprotective mechanisms of Intralipid ® are not totally understood. It has been shown that Intralipid ® can inhibit mitochondrial permeability transition pore opening [24] and reduce mitochondrial superoxide production, and increase pro-survival kinases such as Akt and GSK-3 [23] among other effects [4] [6] [7] [25] [26]. However, the effect of Intralipid ® on post-MI inflammatory MØs has not been investigated.…”
Section: Introductionmentioning
confidence: 99%